Niacin Enhancement for Parkinson’s Disease: An Effectiveness Trial - Chong, Raymond; Wakade, Chandramohan; Seamon, Marissa; Giri, Banabihari; Morgan, John; Purohit, Sharad (Frontiers in Aging Neuroscience, 2021)
We previously reported that individuals with Parkinson's disease (PD) present with lower vitamin B3 levels compared to controls. It may be related to carbidopa interaction, defective tryptophan metabolism and stresses of nightsleep disorder. Vitamin B3 is the energy source for for all cells by producing NAD+ and NADP+ in redox reactions of oxidative phosphorylation. Thus, some symptoms of PD such as fatigue, sleep dysfunction and mood changes may be related to the deficiency of vitamin B3. Here we conducted an effectiveness trial to determine the effect of twelve months low-dose niacin (a vitamin B3 derivative) enhancement in PD individuals. An average of 9 +/- 6-point improvement in the UPDRS III (motor) score was observed after 12 months of daily niacin compared to the expected decline in score (effect size = 0.78, 95% CI = 7-11). Additionally, secondary outcome measures improved. Notably, handwriting size increased, fatigue perception decreased, mood improved, frontal beta rhythm during quiet stance increased, stance postural sway amplitude and range of acceleration decreased. Set shifting however, as measured by the Trail Making-B test, worsened from 66 to 96 seconds. Other measures did not change after 12 months, but it is not clear whether this represents a positive benefit of the vitamin. For example, while the quality of nightsleep remained the same, there was a trend towards a decrease in the frequency of awakening episodes. These results suggest that niacin enhancement has the potential to maintain or improve quality of life in PD and slow disease progression.